Political Entrepreneurship: The Analysis of Its Implications Area to Policy Making - Abdollah Saedi (University of Tehran, 2021)
Objective: Political entrepreneur stimulates fundamental changes in society, which through creative and transformative actions has a tremendous impact on policies and political institutions.Methods: The aim of the present study the implications of political entrepreneurship in policy-making were analyzed using the fuzzy Delphi approach. This research is among the researches mixed with a qualitative and a quantitative approach which is descriptive-survey in terms of purpose, application and nature and method. the statistical population of the study consists of managers of government organizations in Lorestan province. Using the principle of theoretical adequacy and purposeful sampling method, 18 of them were selected as sample members. In the qualitative part of the research, semi-structured (in-depth) interviews were used to collect data, the validity and reliability of which were confirmed using the CVR coefficient and Kappa-Cohen test, respectively, and the data obtained from the interview using the software. Atlas. ti and the coding method were analyzed and the consequences of political entrepreneurship were identified. on the other hand, in the quantitative part, a pairwise comparison questionnaire was used to collect information, the validity and reliability of which were confirmed using content validity and incompatibility rate.Results: The results of the research indicate that based on judgments and surveys of experts, nineteen factors were introduced as the consequences of political entrepreneurship. The results also show that attracting public opinion, developing political life and forming coalitions and groups, accurate internal and external monitoring, policy direction, injecting new and innovative policies and regulating relations in the network are the most important consequences of political entrepreneurship in the field of policymaking.Conclusion: To increase the ability of individuals, groups and parties to continue lawful participation in the political arena, as well as to improve the accountability of the political system, policymakers are advised to pay special attention to entrepreneurs in the field of politics to transform the policy. And policies to solve the problems of the organization and society